Assessment of The Effects of Silicon Application on Growth Parameters and Some Bioactive Components in Hungary vetch (Vicia pannonica Crantz) - Turfan, Nezahat (Turkish Science and Technology Publishing (TURSTEP), 2022)
The objective of this study was to investigate the effect of 10 mM silicon (Si) application on salt stress (50, 100, and 200 mM NaCl) tolerance in Hungarian vetch seedlings (Ege Beyazi-79) based on growth parameters (shoot length and fresh weight, organic dry matter, and moisture), bioactive compounds as chlorophyll, carotenoid, proline, protein, nitrate, and nutrient status. Silicon was applied to the seedlings from the leaves and NaCl from the salt soil, both of which were dissolved in Hoagland solution. The results revealed that the highest shoot length Si+100 mM NaCl was recorded and the highest fresh and dry weight was recorded with length Si+50 mM NaCl. The highest dry matter was obtained from Si and 200 mM NaCl. The highest chlorophyll, carotenoid, proline, protein, and nitrate were obtained from 100 mM NaCl+Si, while the lowest chlorophyll, carotenoid, and nitrate were obtained from 200 mm NaCl and the lowest proline and protein from 100 mM NaCl, respectively. The amount of K, Mg, and S were low in NaCl doses but high in Si and Si + NaCl doses, and P was higher in all groups compared to the control. The content of Na, Co, and Se were high in all groups except Cl 50 NaCl, while Mn, Zn, and Ni were higher in Si and Si + NaCl doses. Silicon content of samples was high at higher NaCl + Si doses. The results provided by this investigating indicated that silicate concentrations positively affected the parameters examined in Hungarian seedlings, and increased the tolerance of seedlings to salt stress.
Keywords: salinityinity si; nutrients; S; growth; Agriculture (General); chemicals; Agriculture; hungarian vetch; S1-972; 6. Clean water